Ashwagandha and stress - Weronika Sobota; Przemysław Piskorz; Katarzyna Zemsta; Michał Zwoliński; Mateusz Tyniec; Kamal Morshed (Kazimierz Wielki University, 2024)
Ashwagandha, also known as Withania somnifera, is an adaptogen gaining popularity as a natural stress reducer. Stress is a common phenomenon caused by factors such as lifestyle, work pressure or social conflict, and has a negative impact on both mental and physical health. In response to these challenges, more and more people are looking for natural solutions, and adaptogens such as ashwagandha offer support in dealing with stress without significant side effects. Scientific research shows that ashwagandha can lower levels of the stress hormone cortisol and improve results on tests assessing stress, anxiety and depression. Numerous studies conducted on both animals and humans confirm its beneficial effects on mental and physical health, including improvement of cognitive functions, sleep quality and emotional well-being. The mechanism of action of ashwagandha includes regulation of the HPA axis, reduction of glucocorticoids and modulation of the immune system. Despite promising results, further research is needed to fully understand its mechanism of action, assess long-term effects, and investigate possible interactions with other drugs. Ashwagandha seems to be a safe and effective agent in the fight against stress, but it is recommended to consult a doctor before starting supplementation.